2012
DOI: 10.7861/clinmedicine.12-5-456
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in drug treatment of obesity

Abstract: ABSTRACT-The prevalence of obesity is rising worldwide, with the UK having the highest prevalence in Europe. Obesity is associated with significant morbidity and has substantial healthcare implications, with current projections estimating that by 2030 obesity will cost the NHS approximately £2 billion each year. Lifestyle modification remains the cornerstone of antiobesity treatment, but drugs can be introduced as adjuncts to assist and maintain weight loss. Some 1.45 million obesityrelated prescriptions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 19 publications
(31 reference statements)
0
41
0
1
Order By: Relevance
“…Antiobesity medications are categorized according to their mode of action, such as inhibitors of fat absorption, inhibitors of the endocannabinoid system, or modifiers of the central nervous system. 390,391 Orlistat is a pancreatic lipase inhibitor that binds to lipase in gut lumen and prevents the hydrolysis and absorption of *30% of the dietary fat contained in a meal. 392 Sibutramine, a selective inhibitor of neurotransmitter (serotonin and norepinephrine) reuptake, acts centrally to reduce food intake.…”
Section: -231mentioning
confidence: 99%
“…Antiobesity medications are categorized according to their mode of action, such as inhibitors of fat absorption, inhibitors of the endocannabinoid system, or modifiers of the central nervous system. 390,391 Orlistat is a pancreatic lipase inhibitor that binds to lipase in gut lumen and prevents the hydrolysis and absorption of *30% of the dietary fat contained in a meal. 392 Sibutramine, a selective inhibitor of neurotransmitter (serotonin and norepinephrine) reuptake, acts centrally to reduce food intake.…”
Section: -231mentioning
confidence: 99%
“…Most of current pharmacological approaches aimed at treating NAFLD consist in inhibiting either 1) fat absorption; 2) inflammation; 3) the endocannabinoid system; or 4) modulating the central nervous system (Carter et al, 2012). Notably, metformin was shown to improve liver injury, but this medication used in type 2 diabetes could not prevent fibrosis in patients with steatosis (Loomba et al, 2009).…”
Section: Treatment Of Mets and Nafldmentioning
confidence: 99%
“…NICE (National Institute for Health and Care Excellence) guidelines limit its use for 2 years. 7 In this study, it is observed that there is significant increase in serum lipids, such as Total Cholesterol (TC), Low Density Lipoprotein (LDL), and Triglycerides (TG) in obese animals. Further, there is a decrease in HDL/ LDL ratio.…”
Section: Discussionmentioning
confidence: 97%